Videotape Recording in Counselling: "What We Know and Where to Find It" - Marks, Stephen E.; Montgomery, John S.; Davis, William L. (Canadian Journal of Counselling and Psychotherapy, 2012)
This paper reviews the use of video tape with respect tothe training- of counsellors and other helping professionals, acceleratingclient growth in counselling and therapy, and improving the functioning ofdifferent types of groups in various settings, and examines the sources ofinformation on VTR. Generally, VTR procedures were found to be veryuseful in promoting desired outcomes in the above three areas. However,it was noted that an overwhelming majority of the information describingthese outcomes was located in journals that were not readily accessible tocounsellors, especially those who worked in non-university settings. Theimplications of this condition are discussed.